2022
DOI: 10.3390/app12031046
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Wool Integral Lipids to Determine Milk Fat Content in Suffolk Down Ewes

Abstract: The identification of higher fat content in ewe milk during lactation can help to improve the nutritional value and quality of the derived dairy products. In this study, we characterized fatty acids from the wool of Suffolk ewes at two time points during lactation and assessed whether they were related to milk fat content through discriminant analysis and, thus, could be potentially used to identify ewes with a high fat content. Eighty single-bearing Suffolk ewes of similar body weight, body score, and age wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 33 publications
(63 reference statements)
0
0
0
Order By: Relevance
“…In addition, the milk fat results in Table 3 were quadratic responses for ewe's milk from the groups, which agree with the results obtained in a previous study by Sanz et al [32], who reported the effects of concentrates on fat in goats. Further, the milk fat content was positively correlated with these fatty acids [33]. This is in line with research by Weimer et al [34], who reported that the ruminal cellulolytic bacterial population increased with higher dietary NDF, which correlated positively with iso C15:0 and iso C17:0.…”
Section: Discussionsupporting
confidence: 90%
“…In addition, the milk fat results in Table 3 were quadratic responses for ewe's milk from the groups, which agree with the results obtained in a previous study by Sanz et al [32], who reported the effects of concentrates on fat in goats. Further, the milk fat content was positively correlated with these fatty acids [33]. This is in line with research by Weimer et al [34], who reported that the ruminal cellulolytic bacterial population increased with higher dietary NDF, which correlated positively with iso C15:0 and iso C17:0.…”
Section: Discussionsupporting
confidence: 90%